Requirement for Pdx1 in specification of latent endocrine progenitors in zebrafish - Kimmel, Robin A (BioMed Central, 2011)
BACKGROUND: Insulin-producing beta cells emerge during pancreas development in two sequential waves. Recently described later-forming beta cells in zebrafish show high similarity to second wave mammalian beta cells in developmental capacity. Loss-of-function studies in mouse and zebrafish demonstrated that the homeobox transcription factors Pdx1 and Hb9 are both critical for pancreas and beta cell development and discrete stage-specific requirements for these genes have been uncovered. Previously, exocrine and endocrine cell recovery was shown to follow loss of pdx1 in zebrafish, but the progenitor cells and molecular mechanisms responsible have not been clearly defined. In addition, interactions of pdx1 and hb9 in beta cell formation have not been addressed. RESULTS: To learn more about endocrine progenitor specification, we examined beta cell formation following morpholino-mediated depletion of pdx1 and hb9. We find that after early beta cell reduction, recovery occurs following loss of either pdx1 or hb9 function. Unexpectedly, simultaneous knockdown of both hb9 and pdx1 leads to virtually complete and persistent beta cell deficiency. We used a NeuroD:EGFP transgenic line to examine endocrine cell behavior in vivo and developed a novel live-imaging technique to document emergence and migration of late-forming endocrine precursors in real time. Our data show that Notch-responsive progenitors for late-arising endocrine cells are predominantly post mitotic and depend on pdx1. By contrast, early-arising endocrine cells are specified and differentiate independent of pdx1. CONCLUSIONS: The nearly complete beta cell deficiency after combined loss of hb9 and pdx1 suggests functional cooperation, which we clarify as distinct roles in early and late endocrine cell formation. A novel imaging approach permitted visualization of the emergence of late endocrine cells within developing embryos for the first time. We demonstrate a pdx1-dependent progenitor population essential for the formation of duct-associated, second wave endocrine cells. We further reveal an unexpectedly low mitotic activity in these progenitor cells, indicating that they are set aside early in development.